Outcomes and patterns of use of Radium-223 in metastatic castration-resistant prostate cancer - Anido-Herranz, Urbano; Fernandez-Calvo, Ovidio; Ruiz-Bañobre, Juan; Martinez-Breijo, Sara; Fernandez-Nuñez, Natalia; Nogareda-Seoane, Zulema; Garrido-Pumar, Miguel; Casas-Nebra, Javier; Muñiz-Garcia, Gloria; Portela-Pereira, Paula; Gomez-Caamaño, Antonio; Perez-Fentes, Daniel Adolfo; et al. (Frontiers in Oncology, 2024)
Radium–223 dichloride (Ra–223) is recommended as a treatment option for metastatic castration resistant prostate cancer (mCRPC) patients with symptomatic bone metastases and no visceral disease, after docetaxel failure, or in patients who are not candidates to receive it. In this study, we aimed to analyze ambispectively overall survival (OS) and prognostic features in mCRPC in patients receiving Ra–223 as per clinical routine practice and identify the most suitable treatment sequence. Patients and methods: Observational, multicentric, ambispective study. Eligibility criteria included mCRPC patients treated with Ra–223, with Eastern Cooperative Oncology Group (ECOG) 0–2, without visceral metastases and no more than three cm involved lymph nodes. Results: 145 patients were included; median age was 73.97 years, Gleason more or equal to 7 in 61 (48%) patients. 73 (81%) had received previously docetaxel. Most important benefit was reached by those patients who received Ra–223 in the second line setting, with a median OS 17 months, (95% CI 12–21), and by patients who received six cycles of treatment, with a median OS 19 months, (95% CI 14–21). Alkaline phosphatase (ALP) decrease was also identified as a prognosis marker. When performing the multivariate analysis, time to develop castration resistant disease longer than 24 months was the most important prognostic factor to predict the evolution of the patients receiving Ra–223. Ra–223 was well tolerated, being thrombocytopenia, anemia, and diarrhea main adverse events. Conclusion: There is a benefit in those patients who received Ra–223 in the second–line setting regardless prior use of docetaxel. In addition, a survival benefit for patients presenting decline in ALP was observed.